PELAKSANAAN MANAJEMEN SUMBER DAYA MANUSIA DALAM MENINGKATKAN MUTU PROFESIONALITAS GURU DI SMP NEGERI 24 MEDAN TAHUN PELAJARAN 2016/2017 - Dewi Sri Indriati Kusuma (Jurnal Sabilarrasyad, 2021)
This study aims to determine how the implementation of human resource management and efforts to improve the quality of teacher professionalism at SMP Negeri 24 Medan. This study uses a qualitative approach. Collecting data using interviews, observation, and documentation. As the subject of this research is the Deputy Head of Curriculum, and teachers. Data was collected through data collection, data reduction, data presentation, conclusion drawing, and verification. From the results of the study, it was found that the process of implementing human resource management functions in improving the quality of teacher professionalism, namely: 1). HR planning at SMP Negeri 24 Medan is good, one of the indications is that it is based on the government and is added by the independence of the principal. 2) Job analysis in the organization to determine the tasks, goals, skills, knowledge, and abilities needed for teachers. 3) Performance Assessment From the results of the improvement in the quality of workers and the work environment here. Improvements in the quality of workers and the work environment. 4) Achievement of the effectiveness of working relations in carrying out their respective duties and professions that have been determined by the Government. 5) Provide the motivation to support the performance of teachers In providing motivation is very important for teachers/educators and staff who take shelter in this school, especially the government system. 6) Enforcing Discipline on teacher performance Discipline is a function of human resources where human resources are very important, because the more disciplined the teachers are, the higher the achievement intended for this school. 7) Holding a meeting In holding this meeting in order to continue the mission and vision that exists in this school to improve the performance of teachers and employees so that in the process of running it, the goals that have been set are achieved. 8) Give rewards to educators and education staff in the form of awards for advancing this school. The conclusion that can be drawn from this research is that the implementation of human resource management has been carried out well and the existing programs are given to this school, but there are several efforts by the principal in improving teacher professionalism. the quality of teacher professionalism.